Research on Artificial Spider Web Model for Farmland Wireless Sensor Network. (22nd March 2018) - Wang, Jun; Gao, Song; Zhao, Shimin; Hu, Guang; Zhang, Xiaoli; Xie, Guowang
Abstract : Through systematic analysis of the structural characteristics and invulnerability of spider web, this paper explores the possibility of combining the advantages of spider web such as network robustness and invulnerability with farmland wireless sensor network. A universally applicable definition and mathematical model of artificial spider web structure are established. The comparison between artificial spider web and traditional networks is discussed in detail. The simulation result shows that the networking structure of artificial spider web is better than that of traditional networks in terms of improving the overall reliability and invulnerability of communication system. A comprehensive study on the advantage characteristics of spider web has important theoretical and practical significance for promoting the invulnerability research of farmland wireless sensor network.